A Smart Distributed Wireless Traffic Management System for Emergency Vehicles Using Zig Bee - sabha, Saqib ul; Dewangan, Shashikant; Ahamad, Syed Tahir (International Journal of Computer Sciences and Engineering, 2025)
These days, the quantity of vehicles has expanded exponentially, yet the bedrock limits of roads and transportation frameworks have not created in an identical approach to proficiently adapt to the quantity of vehicles going on them. There has been huge exploration on Traffic Management Systems utilizing sensor networks to evade congestion, guarantee urgency for emergency vehicles and lower the Average Waiting Time of automobiles at junctions. In order to solve the problem we have developed a distributed embedded electronic system that can considerably solve the problem of ambulances and other emergency vehicles getting jammed at traffic signal lights. The fundamental idea driving this plan is to give a smooth stream to the emergency vehicles like ambulances to achieve the healing facilities in time and along these lines minimizing the delay owing to traffic congestion.